The Dutch house [compact disc, unabridged] : a novel - Patchett, Ann (Harper Collins Publishers, 2019)
At the end of the Second World War, Cyril Conroy combines luck and a single canny investment to begin an enormous real estate empire, propelling his family from poverty to enormous wealth. His first order of business is to buy a lavish estate in the suburbs outside of Philadelphia. Meant as a surprise for his wife, the house sets in motion the undoing of everyone he loves. The story is told by Cyril's son Danny, as he and his older sister, the brilliantly acerbic and self-assured Maeve, are exiled from the house where they grew up by their stepmother. The two wealthy siblings are thrown back into the poverty their parents had escaped from and find that all they have to count on is one another. It is this unshakable bond between them that both saves their lives and thwarts their futures.